Linguistic hybridity and temporal simulation in rewritings of Gulliver's Travels, by Jonathan Swift - Pratas, Jacqueline dos Santos [UNESP]; Amorim, Lauro Maia [UNESP] (Federal Univ Ceara, 2019)
This article analyzes two translations and one adaptation of Gulliver's travels, by Jonathan Swift, a novel originally published in the eighteenth century. The main goal of this study is to observe if translators and adaptors have applied the standard norm of Brazilian Portuguese as a tool to carry out a temporal distancing effect derived from both lexical selection and adoption of particular linguistic structures that attain a semantic, syntactic and stylistic representation of such effect. The results show that, in fact, translators has resorted to strategic use of certain lexical items and grammatical structures that bring out a temporal distancing effect, but some editions have displayed hybrid linguistic structures in line with some informal register, which includes one of the adaptations analyzed, particularly destined for young readers.
Keywords: Translation Studies; Linguistic hybridity norms; Orality markers